Macrophage activating factors produced in the course of murine tularemia: effect on multiplication of microbes - Kovarova, H; Marcela, A; Stulik, J (Archivum immunologiae et therapiae experimentalis, 1992)
Primary F. tularensis infection in mice induces the production of macrophage activating factors (MAFs) by spleen cells. The stimulation of macrophage cytolytic activity (MAF-c) and hydrogen peroxide production (MAF-H2O2) dominates between days 7 and 10 in the course of tularemia. Three various pools of active fractions (10-11, 14-15, 25-28) were fractionated by two-step chromatography. Typical for 10-11 and 14-15 is MAF-c activity whereas in 25-28 prevails MAF-H2O2. Initial concentrated supernatant (day 7 of infection) and individual fractions have been used to raise antibodies KI (anti 10-11) and KII (anti 14-15). Neutralization reactions with specific antibodies indicate the presence of tumor necrosis factor alpha (TNF alpha) in 14-15 (44% inhibitable), interferon gamma (IFN gamma) and interleukin 2 (IL 2) in 25-28 (65% and 30% neutralization, respectively). Utilizing KI and KII, 99% and 90% inhibition of cytolytic activity is reached in 10-11 and 14-15, respectively, in spite of non-specific cross reaction. Western blot analysis of proteins in supernatant on day 7 detects, besides TNF alpha, further protein bands (13, 15.5, 52 and 72 kDa) that seem to be associated with macrophage activation. Significant protective effect against in vivo multiplication of tularemic microbes indicates a certain role of TNF alpha, however, cooperation of other molecules is worth to be taken into consideration.
Keywords: Cell Division; Immunity, Cellular; faktory aktivující makrofágy; interleukin-2; Female; Macrophage Activation; Tularemia; Francisella tularensis; myši inbrední C3H; Mice, Inbred C3H; zvířata; myši; buněčná imunita; Interleukin-2; Mice; TNF-alfa; ženské pohlaví; aktivace makrofágů; peroxid vodíku; Macrophage-Activating Factors; tularemie; interferon gama; Tumor Necrosis Factor-alpha; Animals; Hydrogen Peroxide; Interferon-gamma; buněčné dělení